Economic performance and competitiveness in agriculture: Theoretical approaches - Laurenţiu Rebega (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
In agricultural activity, the performance and competitiveness concepts are interest targets for decisionmakers, regardless of their representation level (production unit and / or product level, activity sector and / or national and / or international level). The way of materializing these two concepts of performance and competitiveness, in the agricultural activity is accomplished through the indicators system used.
Keywords: Q10; Q18; 330; performance; competitiveness; indicators